2012
DOI: 10.1165/rcmb.2012-0012oc
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Adenosine Exposure Causes Lung Endothelial Barrier Dysfunction via Nucleoside Transporter–Mediated Signaling

Abstract: Previous studies by our group as well as others have shown that acute adenosine exposure enhances lung vascular endothelial barrier integrity and protects against increased permeability lung edema. In contrast, there is growing evidence that sustained adenosine exposure has detrimental effects on the lungs, including lung edema. It is well established that adenosine modulates lung inflammation. However, little is known concerning the effect of sustained adenosine exposure on lung endothelial cells (ECs), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Activation of p38 has also been implicated in homocysteine-induced apoptosis of endothelial progenitor cells (Bao et al 2010) and cardiomyocytes (Wang et al 2011). We have shown that sustained exposure to exogenous adenosine causes mitochondrial defects and endothelial apoptosis via mitochondrial oxidative stress-induced activation of p38 (Lu et al 2012, 2013). Active p38 causes apoptosis by direct phosphorylation, and thus inhibition of Bcl-2 (De Chiara et al 2006; Farley et al 2006) and by increasing mitochondrial translocation of Bax (Capano and Crompton 2006).…”
Section: 2 Pulmonary Endothelial Cell Apoptosismentioning
confidence: 99%
“…Activation of p38 has also been implicated in homocysteine-induced apoptosis of endothelial progenitor cells (Bao et al 2010) and cardiomyocytes (Wang et al 2011). We have shown that sustained exposure to exogenous adenosine causes mitochondrial defects and endothelial apoptosis via mitochondrial oxidative stress-induced activation of p38 (Lu et al 2012, 2013). Active p38 causes apoptosis by direct phosphorylation, and thus inhibition of Bcl-2 (De Chiara et al 2006; Farley et al 2006) and by increasing mitochondrial translocation of Bax (Capano and Crompton 2006).…”
Section: 2 Pulmonary Endothelial Cell Apoptosismentioning
confidence: 99%
“…However, most importantly, through the stimulation of CD40, an important TNF receptor, IFN-␥ has been thought to induce the Fas-apoptotic pathway in epithelial cells and stimulate the enlargement of emphysematous airways (110). In addition, extracellular adenosine is often increased during tissue injury and inflammatory insults by the stimulation of ectonucleotidases, CD39 and CD73, or by variations in the activity and expression of adenosine deaminase (76). Recent research has shown that sustained, elevated adenosine exposure may contribute to CS-induced lung endothelial cell apoptosis and emphysema through the activation of p38 and JNK in mitochondria and eventually mitochondrial defects that also lead to cell apoptosis (77).…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%
“…21,22 In this study, we show that pharmacological inhibition of ENT1/2 significantly increased lung adenosine levels and attenuated P. aeruginosa-induced acute lung injury. 21,22 In this study, we show that pharmacological inhibition of ENT1/2 significantly increased lung adenosine levels and attenuated P. aeruginosa-induced acute lung injury.…”
Section: Cfu Of Pa or Equal Volume Of Saline By Intratracheal (It) mentioning
confidence: 53%
“…[18][19][20] We have previously shown that sustained elevated adenosine causes lung endothelial cell barrier dysfunction and apoptosis via ENT1/2dependent mechanisms, 21,22 suggesting that intracellular adenosine uptake is detrimental to lung endothelial cells. ENT1 and ENT2 are major adenosine transporters expressed in lung microvascular endothelial cells and alveolar epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation